2014
DOI: 10.1007/s00726-014-1712-4
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin hydrolase and hyperhomocysteinemia modulate the expression of mouse proteins involved in liver homeostasis

Abstract: The liver is the major contributor to homocysteine (Hcy) metabolism and fatty liver disease is associated with hyperhomocysteinemia. Bleomycin hydrolase (Blmh) is an aminohydrolase that also participates in Hcy metabolism by hydrolyzing Hcy-thiolactone. To gain insight into hepatic functions of Blmh, we analyzed the liver proteome of Blmh(-/-) and Blmh(+/+) mice in the absence and presence of diet-induced (high methionine) hyperhomocysteinemia using 2D IEF/SDS-PAGE gel electrophoresis and MALDI-TOF mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…HHcy was an independent risk factor for cardiovascular diseases. The damage effect of elevated serum Hcy on NAFLD and other liver damage had also been verified both in epidemiological and clinical studies (7,14), and also in animal experiments (26). The range of Hcy in the present study was 13.2 (9.9-15.9).…”
Section: Discussionsupporting
confidence: 82%
“…HHcy was an independent risk factor for cardiovascular diseases. The damage effect of elevated serum Hcy on NAFLD and other liver damage had also been verified both in epidemiological and clinical studies (7,14), and also in animal experiments (26). The range of Hcy in the present study was 13.2 (9.9-15.9).…”
Section: Discussionsupporting
confidence: 82%
“…These findings suggest that while in the kidney and liver the antioxidant defense is enhanced by a high-Met diet, in the brain the antioxidant defense is compromised. The other proteins that were identified as differentially expressed in the kidney (Table 1) were not regulated by the Pon1 −/− genotype and/or high-Met diet in the liver [24] or brain [25]. Pebp1 was up-regulated in the kidney and down-regulated in the brain both by the Pon1 −/− genotype and highMet diet (Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 92%
“…Plasma ApoA-I is also known to be down-regulated in a dietary HHcy mouse model [27], similar to the one used in the present work. Further, in our previous work we found that hepatic ApoA-I is down-regulated by a high-Met diet in wild type mice [24].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Protein extraction. Liver proteins were extracted using the phenol method (Faurobert et al, 2007) as previously described (Suszynska-Zajczyk et al, 2014a). Briefly, liver tissue was disintegrated by grinding with dry ice using a mortar and pestle.…”
Section: Mice and Dietsmentioning
confidence: 99%